2012
DOI: 10.1073/pnas.1202607109
|View full text |Cite
|
Sign up to set email alerts
|

Presensitizing with a Toll-like receptor 3 ligand impairs CD8 T-cell effector differentiation and IL-33 responsiveness

Abstract: The synthetic double-stranded RNA poly(I:C) is commonly used as an adjuvant to boost CD8 T-cell function; however, polyinosinic:polycytidylic acid [poly(I:C)] can also suppress autoimmune disease. The mechanism by which a single adjuvant achieves two distinct immunoregulatory roles is unknown. Although it is clear that coadministration of poly(I:C) with antigen elicits strong adjuvant effects in mice, we found that poly(I:C) injection before antigen substantially reduced antigen-dependent CD8 T-cell responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…A monoclonal murinized IgG1 blocking anti-ST2 Ab and a monoclonal mouse IgG1 Ab directed against an irrelevant human Ag that was used as an isotype-matched control Ab were generated at Amgen (Seattle, WA). Efficacy of the blocking anti-ST2 Ab was demonstrated previously (44,45). A blocking monoclonal anti-IL-6R Ab (clone MR16-1) was provided by Dr. F Sato (Chugai Pharmaceuticals, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A monoclonal murinized IgG1 blocking anti-ST2 Ab and a monoclonal mouse IgG1 Ab directed against an irrelevant human Ag that was used as an isotype-matched control Ab were generated at Amgen (Seattle, WA). Efficacy of the blocking anti-ST2 Ab was demonstrated previously (44,45). A blocking monoclonal anti-IL-6R Ab (clone MR16-1) was provided by Dr. F Sato (Chugai Pharmaceuticals, Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, CMV/IL33 pups were treated from PD 2-4 twice weekly by i.p. injection with a blocking anti-ST2 IgG1 Ab (20 mg/g body weight) (44,45) or an isotype-matched control Ab (20 mg/g body weight). In one experiment, CMV/IL33 pups were injected from PD 3 twice weekly i.p.…”
Section: Micementioning
confidence: 99%
“…[51][52][53][54][55] One of the side effects of poly (I:C) is induction of toxic cytokines, so its use in cancer is limited. [56][57][58] In our study, by encapsulating zoledronic acid and poly (I:C) in LCP, the effective doses of both poly (I:C) and zoledronic acid could be decreased, so this formulation may have less toxic effects. The current peritumoral injection of LCP-poly (I:C)-zoledronic acid in melanoma-bearing mice confirmed the in vivo efficacy of codelivery of poly (I:C) and zoledronic acid by LCP.…”
Section: Codelivery Of Poly (I:c) and Zoledronic Acid Had Superior Cymentioning
confidence: 99%
“…A notable attribute of dual costimulated CD8 T cells in this regard is their ability to be triggered by cytokines in the absence of TCR stimulation. Specifically, stimulation with either IL-12 or IL-2 followed by either of the IL-1 family members IL-33 or IL-36 induces IFN-γ secretion, subsequent induction of MHC class I and II on tumor cells, and degranulation of the CD8 + CTL [134,135]. The underlying mechanism of this TCR-independent process was further studied with the IL-2 plus IL-36 combination, where it was found that IL-2 activates the JAK-STAT pathway that induces transcription of the Il1rl2 gene that encodes the IL-36 receptor [135].…”
Section: Immunotherapies Overcome Tumor-induced Immunosuppressionmentioning
confidence: 99%